2017
DOI: 10.1002/jbmr.3231
|View full text |Cite
|
Sign up to set email alerts
|

Immune Suppressive and Bone Inhibitory Effects of Prednisolone in Growing and Regenerating Zebrafish Tissues

Abstract: Glucocorticoids are widely used as therapeutic agents to treat immune-mediated diseases in humans because of their anti-inflammatory and immunosuppressive effects. However, glucocorticoids have various adverse effects, in particular rapid and pronounced bone loss associated with fractures in glucocorticoid-induced osteoporosis, a common form of secondary osteoporosis. In zebrafish, which are increasingly used to study processes of bone regeneration and disease, glucocorticoids show detrimental effects on bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 81 publications
2
75
0
Order By: Relevance
“…In addition, the study provides evidence that macrophages are crucial early mediators of blastema formation (Petrie et al, 2014). Furthermore, a recent zebrafish study showed, that immune-suppressive treatment using prednisolone leads to decreased bone growth as well as impaired regeneration (Geurtzen et al, 2017). In a zebrafish model of peripheral axonal nerve injury, macrophages rapidly arrive at the lesion site where they engulf axonal debris and invade into the nerve following axon fragmentation (Rosenberg et al, 2012).…”
Section: Monocyte-derived Macrophagesmentioning
confidence: 99%
“…In addition, the study provides evidence that macrophages are crucial early mediators of blastema formation (Petrie et al, 2014). Furthermore, a recent zebrafish study showed, that immune-suppressive treatment using prednisolone leads to decreased bone growth as well as impaired regeneration (Geurtzen et al, 2017). In a zebrafish model of peripheral axonal nerve injury, macrophages rapidly arrive at the lesion site where they engulf axonal debris and invade into the nerve following axon fragmentation (Rosenberg et al, 2012).…”
Section: Monocyte-derived Macrophagesmentioning
confidence: 99%
“…2007 , Oppedal & Goldsmith 2010 ). As in mammals, systemic GC treatment of zebrafish has complex effects, including suppression of the immune response, reduced osteoblast differentiation, and proliferation, and effects on osteoclast activity ( Geurtzen et al . 2017 ).…”
Section: Bone Regeneration and Gcsmentioning
confidence: 99%
“…Tissue-specific manipulations of GR activity have not yet been performed in zebrafish, thus it has to date not been possible to ascertain which of the GC effects on bone, and in particular on osteoblasts, are direct. Interestingly however, in contrast to mammals, prednisolone treatment does not appear to induce osteoblast apoptosis in regenerating zebrafish fins ( Geurtzen et al . 2017 ).…”
Section: Bone Regeneration and Gcsmentioning
confidence: 99%
“…Local metabolism of glucocorticoids in bone cells is controlled by a pair of complementary enzymes, 11β-hydroxysteroid dehydrogenase types 1 and 2 (Hsd11b1 & Hsd11b2), which respectively activate or deactivate glucocorticoid action by metabolizing the interconversion of biologically active or inert forms[6, 7]. Additional pathways of glucocorticoid action are thought to be multiple, including inducing proapoptotic molecules in osteoblasts and osteocytes, and through antagonizing the osteoblastogenic Wnt pathway [4, 8, 9]. There continues to be active work into uncovering pathways of glucocorticoid mechanism at the cellular level[10], including recent claims of enhancing osteoblast activity through heat shock protein 90[11].…”
Section: Mechanism Of Glucocorticoid Actionmentioning
confidence: 99%